Recent Tendencies in Waste-Based Aggregates in Concrete Production - Thomas, Marta (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The development of construction and the growing popularity of concrete as a building material cause a continuous increase in the demand for non-renewable raw material such as aggregate. This paper aims to analyse the possibility of using various alternative aggregates for the production of concrete.
Keywords: concrete aggregate; recycled aggregate; manufactured aggregate; alternative aggregate; concrete; aggregate; kruszywo betonowe; kruszywo recyklingowe; produkcja kruszywa; kruszywa alternatywne; beton; kruszywo